Development and Critical Quality Characterization of Functional UF‐Feta Cheese by Incorporating Probiotic Bacteria. Issue 6 (28th April 2014) - Akbarian Moghari, Ali; Razavi, Seyed Hadi; Ehsani, Mohammad Reza; Mousavi, Mohammad
Abstract: The addition effect of probiotic bacteria ( L actobacillus acidophilus la‐5 and B ifidobacterium lactis  BB‐12) as single and mixed cultures on the physicochemical, proteolysis and sensory characteristics of Iranian UF‐Feta cheese (IUFC) during 60 days of storage at 8C was investigated. Viability of these microorganisms was also determined. The results indicated that the probiotics population remained above 10 6  cfu/g at the storage end. The viability was not significantly affected by co‐culturing. The addition of probiotic adjuncts did not exert significant effect on the proteolysis (water‐soluble nitrogen and trichloroacetic acid‐soluble nitrogen indices), syneresis, pH and other physicochemical properties. The presence of B . lactis  BB‐12 in the cheese caused a significant increase ( P  < 0.05) in flavor and overall acceptability. However, the cheese containing both probiotic strains were preferred over the other manufactured cheese. IUFC is a suitable carrier of L . acidophilus la‐5 and B . lactis BB12 with an increased flavor and overall acceptability. Practical Applications: Along with the growing consumer awareness about the health benefits of probiotics, there is a greater interest in developing new probiotic foods other than yoghurt and fermented milk. In response to this demand, the results of the present study confirm that UF‐Feta cheese can be a good carrier of the probiotic bacteria L . acidophilus la‐5 and B . lactis  BB‐12. In addition, these findings can be useful for the incorporation of probiotics in other types of cheese with general specifications (pH, dry matter, salt content and etc) similar to those of the UF‐Feta cheese.